Development of E-LKPD Based on Ecopreneurship in Islamic Context to Increase Entrepreneurial Interest in Changes in Environmental Concepts - Fuadah, Armita Indah; Zulfiani; Solihin (Biosfer: Jurnal Pendidikan Biologi, 2024)
Integrating entrepreneurship into various subjects, particularly biology, helps foster creativity and problem-solving skills. Often seen as theoretical, biology can link to entrepreneurship through eco-friendly activities. This study aims to develop electronic worksheets (E-LKPD) as a learning tool based on ecopreneurship to increase students' interest in entrepreneurship, especially in waste recycling, within an Islamic context. The method used is Research and Development (R&D) with a 4-D development model Thiagarajan (Define, Design, Develop, and Disseminate), which is modified into 3D (without Disseminate). The instruments used in this research included a checklist of student’s worksheets, interview sheets, content validity for student worksheets, teacher and student response questionnaires, and pre-questionnaire and post-questionnaire entrepreneurship interests. The development process involved validity testing by nine experts, readability testing by 15 students, and field trials by one biology teacher and 36 students. The results showed that the E-LKPD had a very high validity and readability. Teachers and students gave positive feedback during the field trials, and the entrepreneurial interest of students increased significantly, moving from a high to a very high category after using E-LKPD. It indicates that the electronic worksheets are valid and practical for enhancing entrepreneurial interest within biology, particularly in environmental awareness and sustainability. E-LKPD based on ecopreneurship also successfully integrates Islamic values, such as responsibility and concern for the environment. In this way, students not only get academic knowledge, but also entrepreneurial skills.